Groups with the minimality condition for infinitely generated subgroups - Shaptala, V. P. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
We establish that, in the class of locally almost solvable groups, the minimality condition for infinitely generated subgroups is equivalent to the minimality condition for (all) subgroups.